An Analysis of the Teachers' Climate Change Awareness - Burckin Dal; Nilay Ozturk; Umut Alper; Duygu Sonmez; Aytekin Cokelez (Athens Institute for Education and Research, 2015)
This paper reports a study conducted to investigate social studies and science teachers' awareness on climate change and how the professional development workshop "Awareness and Adaptation to Climate Change" affects teachers' awareness level. For this purpose, a total of 101 teachers from 8 different cities and 4 geographical locations participated in the workshop and took part in the study. For data collection purposes, the Awareness to Climate Change Questionnaire (ACCQ) was used. The analysis revealed no statistical difference among participating teachers' awareness level based on pre-test scores. However, further analysis indicates an increase in awareness on climate change among participating teachers upon completion of the professional development workshops.